Social Security's Five OASI Inflation Indexing Problems - Michael C. Lovell (Kiel Institute for the World Economy (IfW), 2008)
This paper examines five problems with the inflation indexing procedures used by the Social Security Administration of the United States in taking inflation into account when calculating Old Age and Survivors Insurance (OASI) Benefits. Because of Problem #1, the commingling of unindexed with indexed earnings, a retiree born in 1930 who continued in a high earning career until age 75 receives an annual benefit more than 1,800 larger than would have been generated with full indexing. As a result of Problems #2 and #4 your OASI check will be larger if wage inflation happens to be extra high in your 60th year or if price inflation is exceptionally low in your 61st year. Because of the indexing problems, the percentage increase in your inflation (CPI-W) adjusted benefit if you elect to postpone retirement and the start of OASI benefits will depend in part on the pace of inflation. While inflation indexing problems do not attract much attention in normal times, they can contribute to serious short-run financial instability for the OASI trust fund in periods of substantial inflation or deflation.
Keywords: H55; 330; Social Security; inflation; indexing; Gesetzliche Rentenversicherung; Alterssicherung; Inflation; Indexierung; USA